Development of a Mental Model Diagnostic Test using Predict, Observe, Explain (TDM-POE) on Voltaic Cell Materials - Rahayu, Dea Santika; Rahayu, Dita Puji; Yanti, Meili (Journal of Tropical Chemistry Research and Education, 2024)
Understanding chemical concepts as a whole show that students can connect three levels of chemical representation. The three levels in chemical representation are related and reflected in students' mental models. A teacher must know the student's mental model as a reflection of learning. This research aims to develop an instrument for students' mental models on voltaic cell submaterials using the prediction-observation-explanation (TDM-POE) mental model diagnostic test. The method used in this research is the research and development method using the Analysis, Design, Develop, Implement, and Evaluate (ADDIE) development model. The instrument was validated by five validators consisting of four lecturers in the Department of Chemistry Education and one chemistry teacher at school. Validity is determined by content validity response. Then, the instrument was tested on class XII students who had received learning about voltaic cells. The instrument consists of four questions for four concepts: voltaic cell construction, calculating standard cell potential values, voltaic cells in alkaline batteries, and corrosion phenomena. Each question consists of 3 stages, namely, the first stage contains questions about predicting phenomena (predict), the second stage contains video or image observations (observe), and the third stage contains detailed explanations (explanation). The validation results show that the validity of the TDM-POE instrument obtained a score of 0.99, which is categorized as valid. So, the TDM-POE instrument can be used to understand chemical concepts.